Impact of Cassava Leaf Meal as a Rice Bran Substitute and Enzyme Supplementation on Lymphoid Organ Weight and Digestibility in Broiler Chickens - Muhammad Ridla; Ririn Angriani; Widya Hermana (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
Cassava leaves are a potential alternative feed ingredient due to their high levels of crude protein and energy. However, their utilization in poultry feed is constrained by factors such as cyanic acid, fiber content, and nutrient digestibility. This study aimed to investigate the impact of including cassava leaf meal (CLM) as a rice bran substitute and enzyme supplementation on lymphoid organ development and metabolizable energy parameters in broiler chickens. A 2x3 completely randomized factorial design was conducted using 48 Cobb-strain broilers unsexing at 35 days old. The treatments included different levels of CLM and enzyme (NSP and protease) supplementation at a dose of 250 g/ton of feed. The treatments consisted of R0E0: 0% CLM without enzyme, R0E1: 0% CLM with enzyme, R1E0: 1.5% CLM without enzyme, R1E1: 1.5% CLM with enzyme, R2E0: 3% CLM without enzyme, and R2E1: 3% CLM with enzyme. The variables assessed were lymphoid organ development (thymus, bursa Fabricius, and spleen) and metabolizable energy parameters (Apparent Metabolizable Energy (AME), True Metabolizable Energy (TME), Apparent Metabolizable Energy Corrected to Nitrogen (AMEn), and True Metabolizable Energy Corrected to Nitrogen (TMEn)). The data were subjected to analysis of variance (ANOVA) with post-hoc tests conducted for significant differences. Results indicated no interaction between CLM and enzymes in lymphoid organ development and energy metabolizable. The inclusion of CLM led to a reduction in AME and TME (p<0.05). However, enzyme supplementation significantly increased the relative weight of lymphoid organs (thymus, bursa Fabricius, spleen) and metabolizable energy parameters (AME, TME, AMEn, and TMEn) (p<0.05). Importantly, the inclusion of CLM up to a level of 3.0% did not negatively impact the health of broiler chickens. Furthermore, the addition of enzymes effectively mitigated the negative effects associated with CLM inclusion in the feed, suggesting their potential as a strategy to improve feed utilization in broiler production systems.